2016
DOI: 10.1002/art.39489
|View full text |Cite
|
Sign up to set email alerts
|

Production of RANKL by Memory B Cells: A Link Between B Cells and Bone Erosion in Rheumatoid Arthritis

Abstract: Objective Rheumatoid arthritis (RA) is a systemic autoimmune disease that often leads to joint damage. The mechanisms of bone damage in RA are complex, involving activation of bone-resorbing osteoclasts (OCs) by synoviocytes and Th17 cells. This study was undertaken to investigate whether B cells play a direct role in osteoclastogenesis through the production of RANKL, the essential cytokine for OC development. Methods RANKL production by total B cells or sorted B cell subpopulations in the peripheral blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
119
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 148 publications
(126 citation statements)
references
References 49 publications
2
119
0
5
Order By: Relevance
“…During the preparation of this manuscript, Meednu et al very recently showed that combinatorial stimulation with anti-CD40 and phorbol 12-myristate 13-acetate (PMA) induced RANKL expression in memory B cells and promoted osteoclast differentiation in vitro [36]. These impressive findings emphasize a potential role of effector B cells in osteoclastogenesis involved in RA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the preparation of this manuscript, Meednu et al very recently showed that combinatorial stimulation with anti-CD40 and phorbol 12-myristate 13-acetate (PMA) induced RANKL expression in memory B cells and promoted osteoclast differentiation in vitro [36]. These impressive findings emphasize a potential role of effector B cells in osteoclastogenesis involved in RA.…”
Section: Discussionmentioning
confidence: 99%
“…These impressive findings emphasize a potential role of effector B cells in osteoclastogenesis involved in RA. Here, instead of fixed cells frequently used in the co-culture system [36, 37], we applied the novel system using macrophage RAW264 Venus reporter cells to monitor osteoclastogenesis co-cultured with live B cells, and showed that switched-memory B cells did facilitate osteoclastogenesis (Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of T cells, particularly those of the proinflammatory Th17 cell subset, fosters the expression of RANKL and also induces osteoclastogenesis (48). Furthermore, previous studies have shown that activated B cells can induce osteoclast differentiation, an effect mediated through increased expression of RANKL on their surface (50,51). Furthermore, previous studies have shown that activated B cells can induce osteoclast differentiation, an effect mediated through increased expression of RANKL on their surface (50,51).…”
mentioning
confidence: 99%
“…Given that elevated serum and tissue RANKL concentration were detected in RA patients (19, 68-71), rheumatoid bone and joint destruction in RA are likely mediated by RANKL-induced OC differentiation (Figure 1). Many cell types, including T lymphocytes, B cells and osteoblasts (OB), release RANKL during the course of RA (72, 73). Several cellular factors including PTH (74) and CXCL16 are involved in the regulation of RANKL (20).…”
Section: Rankl In Ra Pathogenesismentioning
confidence: 99%
“…RANKL-expressing Th17 cells stimulate mature but non-resorptive osteoclasts to resorb bone (87, 88). In addition, RANKL secreted by memory B cells promotes bone erosion in RA (73) and OC formation in an ovariectomy model of osteoporosis (89). Lastly, RANKL was known to induce immune tolerance by promoting the differentiation of Treg cells (90-92).…”
Section: Rankl In Ra Pathogenesismentioning
confidence: 99%